A dilute gold nanoparticle suspension as small‐angle X‐ray scattering standard for an absolute scale using an extended Guinier approximation. Issue 2 (26th March 2019) - Mohammed, Ahmed S. A.; Carino, Agnese; Testino, Andrea; Andalibi, Mohammad Reza; Cervellino, Antonio
Abstract : A gold nanoparticle suspension is established as an absolute intensity standard for small‐angle X‐ray scattering experiments on dilute liquid suspensions. An extension of the Guinier method was used to achieve maximum precision on the extrapolated intercept at Q = 0. Abstract : In this article, a practical procedure for absolute intensity calibration for small‐angle scattering (SAXS) studies on liquid microjets is established. A gold nanoparticle suspension is used as standard so that the intercept at Q = 0 of the SAXS scattering curve provides a scaling reference. In order to obtain the most precise extrapolation at Q = 0, an extension of the Guinier approximation has been used, with a second‐order term in the fit that adapts to a larger Q range.